Histometabolic Tumor Imaging of Hypoxia in Oral Cancer: Clinicopathological Correlation for Prediction of an Aggressive Phenotype - Morand, Grégoire B.; Broglie, Martina A.; Schumann, Paul; Huellner, Martin W.; Rupp, Niels J. (Frontiers in Oncology, 2020)
Introduction: Fluorodeoxyglucose-positron emission tomography (FDG-PET) is a widely used imaging tool for oral squamous cell carcinoma (OSCC). Preliminary studies indicate that quantification of tumor metabolic uptake may correlate with tumor hypoxia and aggressive phenotypes. Methods: Retrospective review of a consecutive cohort of OSCC with available pretherapeutic FDG-PET/CT, treated at the University Hospital Zurich. Clinico-pathologico-radiological correlation between maximum standard uptake value (SUVmax) of the primary tumor, immunohistochemical staining for hypoxia-related proteins GLUT1 and HIF1a, depth of invasion (DOI), lymph node metastasis, and outcome was examined. Results: Positive staining for GLUT1 and HIF1a on immunhistopathological analysis correlated with increased SUVmax on pretherapeutic imaging and with increased DOI (Kruskal-Wallis, P=0.037 and P=0.008, resp.). SUVmax and DOI showed a strong positive correlation (Spearman Rho, correlation coefficient= 0.451, P= 0.0003). An increase in SUVmax predicted nodal metastasis (Kruskal-Wallis, P=0.017) and poor local control (Log rank, P=0.047) Conclusion: In OSCC, FDG-PET-derived metabolic tumor parameter SUVmax serves as a surrogate marker for hypoxia and can be used to predict tumor aggressiveness, with more invasive phenotype and poorer local control.